A etnomatemática como ferramenta do saber/fazer matemático nos artesanatos dos bichinhos de madeira do povo Guarani - Rhuan Guilherme Tardo Ribeiro; Josie Agatha Parrilha da Silva (Revista da Faculdade de Educação (Universidade do Estado de Mato Grosso), 2023)
This research has its theoretical-methodological character based on assumptions of the Ethnomathematics Program, in the “Dambrosian” aspect, and dialogues with the knowledge of the original peoples, how they organize their daily lives and, in turn, develop their mathematical knowledge/doing about their sociocultural needs. In this sense, looking at other ways of knowing/doing mathematics is recognizing that each social group has a traditional education system, built from the strengthening of its sociocultural aspects. Our focus is on the Guarani knowledge involved in the production of handicrafts and accessories, their artisanal know-how, which is passed down from generation to generation, in the arts/techniques of artisans and artisans. As a result of the investigation, we present a study on handicrafts and ornaments produced by Guarani indigenous people from the Tekoha Ocoy community, in the municipality of São Miguel do Iguaçu, in western Paraná.